Role of surface morphology on bed material activation during indirect gasification of wood. (1st February 2023) - Faust, Robin; Valizadeh, Ali; Qiu, Ren; Tormachen, Alyona; Maric, Jelena; Vilches, Teresa Berdugo; Skoglund, Nils; Seemann, Martin; Halvarsson, Mats; Öhman, Marcus; Knutsson, Pavleta
Highlights: Olivine and feldspar exhibit similarities regarding their ash layer formation. Formation of ash layers is more pronounced on convex areas of bed particles. A layer of Mn and Fe causes the particles to exhibit an oxygen carrying ability. Alkali and alkaline earth metals are present on the surface of the bed particles. Abstract: Olivine and alkali-feldspar were utilized in separate campaigns in an indirect dual fluidized bed gasification campaign with woody biomass as fuel. After three days, both bed materials were reported to be active towards tar removal and exhibited oxygen-carrying abilities and had formed an ash layer consisting of an outer ash deposition layer and an inner interaction layer. X-ray microtomography analysis concluded that a preferred deposition of ash happens onto convex regions of the bed particles, which results in an increase in thickness of the ash layer over convex regions. This effect is most pronounced for the outer layer which is a product of ash deposition. The inner layer exhibits a homogeneous thickness and is probably formed by interaction of Ca from the outer layer with the particles. Transmission electron microscopy revealed the presence of Fe and Mn on the surface of the particles in a solid solution with Mg. The oxygen-carrying effect which is found for aged particles is therefore attributed to the presence of Fe and Mn on the surface of aged particles. Alkali were found on the surface of both particles which are likely contributing to the catalytic activity of the material towards tar removal.